Wpływ koniunktury gospodarczej na import i eksport surowców energetycznych - Stefański, Ryszard (The Influence of the Business Cycle on Import and Export of Energy Resources, 2009)
The aim of the paper is to analyze and interpret relationships between the business cycle and international exchange of energy resources. Theoretical models suggest that fluctuations on demand of energy resources depend on fluctuation of global production. The demand's fluctuations on natural resources distinguish higher amplitude than production's fluctuations. The results of analysis prove that the domestic and foreign business situation influences moderately import and export of energy resources. The prices of natural resources influences in a small way the volume of import and export of energy resources.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 850-858